Efficiency analysis of using a combination of air and ground heat pumps for heating and ventilation - Bezrodny, M.K.; Oslovskyi, S.А. (KU publ., 2021)
The article considers the energy efficiency of the combination of two most common heat sources for heat pumps, namely soil and ambient air. A feature of such a system is the connection of air and ground heat pumps in series with water. A computational model of the proposed system is developed, based on the system of equations for heat and material balances of the system. The result of the analysis was a system of equations, the analysis of which made it possible to study the two main characteristics of energy efficiency, namely, the relative heat load of the ground heat exchanger and the specific total costs of external work for the drive of the system, depending on the depth of utilization of the heat of ventilation emissions. It is shown that a positive effect from the use of a heating and ventilation system with two heat pumps, both in terms of energy and investments, can be achieved with the utilization depth of ventilation emissions corresponding to the condition of equality of the conversion factors for air and ground heat pumps.
Ғимаратты жылыту және желдету үшін ауа және жердегі жылу сорғыларының комбинациясын пайдалану тиімділігін талдау.
Анализ эффективности использования комбинации воздушного и грунтового тепловых насосов для отопления и вентиляции здания.
Keywords: heat pump; ventilation emissions; soil heat; energy efficiency; specific work; atmospheric air; combination of heat sources